A theoretical explanation for the Central Molecular Zone asymmetry - Sormani, Mattia C.; Treß, Robin G.; Ridley, Matthew; Glover, Simon; Klessen, Ralf S.; Binney, James; Magorrian, John; Smith, Rowan (Monthly notices of the Royal Astronomical Society, 2017)
Abstract: It has been known for more than 30 yr that the distribution of molecular gas in the innermost 300 parsecs of the Milky Way, the Central Molecular Zone, , is strongly asymmetric. Indeed, approximately three quarters of molecular emission come from positive longitudes, and only one quarter from negative longitudes. However, despite much theoretical effort, the origin of this asymmetry has remained a mystery. Here, we show that the asymmetry can be neatly explained by unsteady flow of gas in a barred potential. We use high-resolution 3D hydrodynamical simulations coupled to a state-of-the-art chemical network. Despite the initial conditions and the bar potential being point symmetric with respect to the Galactic Centre, asymmetries develop spontaneously due to the combination of a hydrodynamical instability known as the ‘wiggle instability’ and the thermal instability. The observed asymmetry must be transient: observations made tens of megayears in the past or in the future would often show an asymmetry in the opposite sense. Fluctuations of amplitude comparable to the observed asymmetry occur for a large fraction of time in our simulations, and suggest that the present is not an exceptional moment in the life of our Galaxy.